A new type of bionic grid plate—The compressive deformation and mechanical properties of the grid beetle elytron plate. (January 2022) - Hao, Ning; Chen, Jinxiang; Song, Yiheng; Zhang, Xiaoming; Zhao, Tidong; Fu, Yaqin
To develop lightweight and biomimetic structural materials, in this paper, the compressive deformation and mechanical properties of the grid beetle elytron plate (GBEP) with the same core volume as the end-trabecular beetle elytron plate (EBEP) under compression were investigated for the first time. (1) The B-type deformation mode of trabeculae is clarified, which is a higher stage of independent deformation than the Φ-type deformation mode in the beetle elytron plate (BEP). Additionally, the four deformation modes of the BEP are divided into three stages in succession from easy to difficult: C-type, Φ-type and S (B)-type deformation. This paper verifies that the compressive strength and energy absorption capacity of the GBEP increase by 35% and 87%, respectively, relative to those of the grid plate (GP) with the same volume. (2) Although the number of trabeculae of the GBEP is significantly less than that of the EBEP, each trabecula in the GBEP has one more honeycomb wall constraint than each trabecula in the EBEP. The increase range of the compressive properties of the GBEP relative to the GP is greater than that of the EBEP relative to the honeycomb plate (HP). This confirms the prediction that the compressive properties can be effectively improved by appropriately increasing the constraints on the trabeculae. This paper deepens and enriches the knowledge regarding the biomimetic application system of BEPs, lays the foundation for GBEPs, whose preparation is convenient, and accelerates the applications of GBEPs.